A Single-Center Experience with a Pregnant Immigrant Population and Zika Virus Serologic Screening in New York City - Merriam, Audrey A.; Nhan-Chang, Chia-Ling; Huerta-Bogdan, B. Isabel; Wapner, Ronald; Gyamfi-Bannerman, Cynthia (American Journal of Perinatology, 2020)
Objective Our institution is in an area of New York City with a large population of immigrants from Zika virus endemic areas. With the recent Zika virus outbreak, we sought to examine our center's experience with screening for Zika virus and outcomes among patients who tested positive for the disease during pregnancy.Study Design We performed a chart review of all pregnant patients who tested positive (positive serum or urine polymerase chain reaction [PCR]) or presumed positive (immunoglobulin M [IgM] enzyme-linked immunosorbent assay [ELISA] positive or IgM ELISA equivocal with positive plaque reduction neutralization test) for Zika virus. All tests were performed by the Department of Health (DOH) and followed Centers for Disease Control and Prevention guidelines in effect at the time of specimen collection. Testing of cord blood, placenta, and/or neonatal blood were/was performed by the DOH for New York County. Prenatal ultrasounds for fetal head size and surveillance for calcifications were performed by maternal–fetal medicine specialists. Infant head ultrasound results were included when available.Results Between March 2016 and April 2017, 70 pregnant patients were positive or presumed positive for Zika infection during pregnancy. Of those, 16 women had positive urine or serum PCR and the remaining 54 were presumed positive. Among positive cases, five women tested positive via urine PCR only, nine women tested positive via serum PCR only, and two women had both positive urine and serum PCR. Fifteen of 67 infants (22%) born during the study period were born to mothers with positive urine or serum PCR testing. Sixty-five newborns were clinically normal with normal head measurements. Of the intracranial ultrasound performed, one infant had a grade 1 intraventricular hemorrhage, four had incidental choroid plexus cysts, and one had severe ventriculomegaly that was also noted antenatally. There were 2 positive and 15 equivocal infant serum IgM samples and 1 positive placental PCR from these pregnancies. There were four pregnancy terminations and two cases with fetal anomalies in this population that were split evenly between patients who tested positive and those who tested presumed positive for Zika virus during pregnancy.Conclusion We found no differences in pregnancy or neonatal outcomes between women who tested positive and presumed positive for Zika virus during pregnancy. Testing of infants and placenta tissue after delivery was largely inconclusive. Improvement in testing for Zika virus infection is needed to determine which pregnancies are at risk for congenital anomalies. Further research is still needed to determine which children are at risk for poor neurodevelopmental outcomes related to Zika virus and how to best coordinate care among the immigrant population during a new disease epidemic.
Keywords: Zika virus; immigrant population; ultrasound; perinatal; infection; screening